Factors Influencing Consumer Interest in Visiting Coffee Shops in Medan - Lubis, Andi Reza Syahputra; Effendi, Ihsan; Aisyah, Nur; Aulia, Muhammad Reza (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study was to analyze the factors influencing consumer interest in visiting coffee shops in Medan. This study focused on five main variables: product quality, price, service, atmosphere, and product innovation. The research sample was determined based on the minimum criteria for multiple linear regression analysis, which was at least 5–10 times the number of research variable indicators, resulting in a sample size of 50 respondents. Respondents were coffee shop consumers in Medan who had visited Baraka, Sekata, Heloki, and Dominico coffee shops. Consumer interest in visiting coffee shops was primarily influenced by service quality and atmosphere, while product quality played a smaller role. Price and product innovation were insignificant, indicating that experience and comfort were more important. Therefore, coffee shops in Medan should focus on improving service, product quality, and atmosphere rather than lowering prices or increasing innovation.